Research on Multipath Correlated Imaging with the Grayscale Target in Endoscopic Applications - Jiejie Liu; Yanfeng Bai; Xianwei Huang; Wei Tan; Suqin Nan; Xuanpengfan Zou; Xiquan Fu (Applied Sciences, 2021)
The application of correlated imaging in endoscope, one of the research hotspots, may lead to multipath effect in the closed endoscopic environment. The model of multipath correlated imaging with a grayscale object is given, where the mismatch ratio and the reflection ratio are two key factors affecting imaging quality. The theoretical and experimental results show that multipath effect has an influence on the grayscale distribution and imaging quality of the reconstructed image, and the effect of the mismatch ratio is stronger than that of the reflection ratio. The conditions that the disturbance from multipath effect can be ignored in endoscopic applications are given.